Tingkat Kepuasan Pasien Terhadap Kualitas Pelayanan di IGD RSUD Ciawi - Natasya Rahma Dewi Pawestri; Loisa, Riris (Jurnal Ners, 2025)
Abstract: Patient satisfaction is always related to the quality of health services. The quality of health services is an important indicator that must be a concern of hospitals as providers of public health services. Patients in the Ciawi Hospital Emergency Room reach 1700 patients every month, and there are several patient complaints. The purpose of this study was to analyze the relationship between sociodemographic factors and the level of patient satisfaction in the Emergency Room of RSUD Ciawi, as well as analyzing the level of patient satisfaction with the quality of service in the Ciawi Hospital Emergency Room based on the five aspects of service quality. This research used a quantitative descriptive approach. The population of this study was 1700 emergency room patients at Ciawi Hospital in a month, and the sample of this study consisted of 94 emergency room patients at Ciawi Hospital. The research data was collected through the use of a questionnaire, and then the Cronbach’s alpha coefficient was calculated using SPSS software to process the reliability test data.